1998
DOI: 10.4319/lo.1998.43.4.0679
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic regulatory model of phytoplanktonic acclimation to light, nutrients, and temperature

Abstract: A new regulatory model can describe acclimation of phytoplankton growth rate (p), chlorophyll a : carbon ratio and nitrogen: carbon ratio to irradiance, temperature and nutrient availability. The model uses three indices of phytoplankton biomass-phytoplankton carbon (C), phytoplankton nitrogen (N), and chlorophyll a (Chl). The model links the light-saturated rate of photosynthesis to N: C, requires that Chl a synthesis be coupled to nitrogen assimilation, and includes several regulatory features. These include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
868
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 842 publications
(925 citation statements)
references
References 75 publications
27
868
1
4
Order By: Relevance
“…As the effects of nutrient supply and phytoplankton taxonomic composition are confounded in our field study, we cannot distinguish their respective role in controlling P Bm . It was demonstrated that N limitation in microalgae limits the amount of Chla and RubisCO, the key enzyme involved in photosynthetic fixation of carbon dioxide (CO 2 ) (Geider and MacIntyre, 2002;Turpin, 1991) and that P Bm parallels N content in N-limited algae (Geider et al, 1998). Moreover, P starvation limited also P Bm and the contribution of RubisCO to cell protein in Dunaliella tertiolecta Butcher (Geider et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the effects of nutrient supply and phytoplankton taxonomic composition are confounded in our field study, we cannot distinguish their respective role in controlling P Bm . It was demonstrated that N limitation in microalgae limits the amount of Chla and RubisCO, the key enzyme involved in photosynthetic fixation of carbon dioxide (CO 2 ) (Geider and MacIntyre, 2002;Turpin, 1991) and that P Bm parallels N content in N-limited algae (Geider et al, 1998). Moreover, P starvation limited also P Bm and the contribution of RubisCO to cell protein in Dunaliella tertiolecta Butcher (Geider et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Main environmental factors influencing P Bm in cultures are temperature and nutrient availability (Geider and MacIntyre, 2002). A reduction of P Bm is observed in nutrient-limited algae (Geider et al, 1998;Greene et al, 1991). At the community level, it has occasionally been demonstrated that larger cells sustain higher P Bm than smaller cells (Cermeño et al, 2005;Peltomaa and Ojala, 2010), but field studies attempting to relate the compound photosynthetic response on the taxonomic composition of the phytoplankton assemblage are rare (Segura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since CChl changes due to the effects of photoacclimation, it is modelled according to the formulations given in Geider et al (1997) and Geider et al (1998).…”
Section: Coupling Between Ecophysiological and Biogeochemical Modelmentioning
confidence: 99%
“…The model is based on this optimality argument, and some physiological detail has been sacrificed to allow the optimality argument to be used. One important simplification is that carbon metabolism and nitrogen metabolism are treated as being independent, whereas recent empirically based model structures allow carbon acquisition to depend on cell nitrogen (Sciandra et al 1997;Geider et al 1998). Explicit modeling of physiological feedbacks between internal nitrogen stores and external ammonium and nitrate pools (Flynn et al 1997) has also been suppressed for biogeochemical clarity.…”
Section: Acknowledgmentsmentioning
confidence: 99%